IMPROVING STUDENTSâ MOTIVATION IN SPEAKING ENGLISH THROUGH ACTIVE LEARNING STRATEGY - Badroeni, Badroeni (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
This research is to analyze the implementation of active learning strategy in improving studentsâ motivation in speaking English. Active learning strategy was intended to improve studentsâ motivation. The researcher undertakes in three procedures; trading place, question students have, and action learning. In this research, the researcher uses classroom action research in three cycles. The model used is Kemmis and Mc Taggart. The stages are four stages including planning, action, observation, and reflectionThe calculation of studentâs mean score, the data of motivation improvement in every cycle;the pre-testis 54.65%, the cycle 1 is 82.55%, cycle 2 is 92.35 and cycle-3 is 98.60.Every cycle is done in three meetings. The test is given in four times; the first is pre-test, the second test is in the end of cycle 1, the third test is in the end of cycle 2, and the forth test is in the end of cycle 3. The result of research indicates the improvement of studentsâ speaking ability. In this case, quantitative data in every cycle describes the improvement. The pre test has average score 31, cycle 1 has average score 57.83, cycle 2 has average score 69.17, and cycle three has average score 95.34.Keywords: Motivation, speaking ability, active learning strategy.